THE INFLUENCE OF STUDENT CONFIDENCE AND EMOTIONAL INTELLIGENCE ON LEARNING OUTCOMES OF CLASS - Zakira Az Zahro; Siti Sri Wulandari (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to analyze the Influence of Students' Self-Confidence and Emotional Intelligence on Learning Outcomes in the Basics of Office Management and Business Services at SMK Ketintang Surabaya. The research method used is a quantitative approach. The population involved in this study were all students of class X MP (Office Management) as many as 176 students, with a sample of 176 students determined using a saturated sample technique to obtain comprehensive results. The data analysis used was multiple linear regression analysis to test the extent to which the independent variables (self-confidence and emotional intelligence) affect the dependent variable (learning outcomes). The results showed that self-confidence had a significant effect on learning outcomes with a regression coefficient of 0.108, while emotional intelligence had a stronger effect with a coefficient of 0.124. Together, the two variables contributed 49.4% to the learning outcome variable, the rest of which was influenced by other factors not included in this study. This finding indicates that although both factors have a positive influence, emotional intelligence plays a more dominant role in improving students' academic achievement. The conclusion of this study is that there is a significant relationship between self-confidence and emotional intelligence with learning outcomes, so schools are advised to develop programs to strengthen students' psychological aspects to support learning success, both partially and simultaneously.